'I am Limpeh (your father)!' Parodying Hegemony, Anti-nostalgic Cultural Insurgency and the Visual Amplification of Lee Kuan Yew in Late Authoritarian Singapore - Khiun, Liew Kai (2015)
The soft-authoritarian and severe image of contemporary Singapore has often been associated with the imposing and paternalistic presence of Lee Kuan Yew who has overseen the city-state as prime minister and subsequently, senior statesman since 1959. Unlike the statues and street-names dedicated to other founding leaders in newly decolonized countries, Lee has consciously discouraged any public portraitures of himself in Singapore. However, as his presence fades with ailing health in the recent years, his images are beginning to surface in figurines, coffee table books and even street art. Over in the social and alternative media, there is an increasingly more irreverent use of the Hokkien/Minan term ‘limpeh’ or ‘your father’ as parodies of Lee’s unyielding paternalism. As a masculinistic self-assertion of one’s authority, ‘limpeh’ is often crudely associated with the Hokkien/Minan-speaking ethnic Singaporean Chinese working class. Singaporeans have also recognized the characteristics of ‘limpeh’ with the authoritarian legacy of Lee who had displayed little mercy in crushing his political rivals and pushing his social vision to society. In this respect, these popular communications can be seen as the cacophony of emerging voices of the city-state in a late authoritarian phase.